A Thinning Method of Linear And Planar Array Antennas To Reduce SLL of Radiation Pattern By GWO And ICA Algorithms - H. Rezagholizadeh; D. Gharavian (AUT Journal of Electrical Engineering, 2018)
In the recent years, the optimization techniques using evolutionary algorithms have been widely used to solve electromagnetic problems. These algorithms use thinning the antenna arrays with the aim of reducing the complexity and thus achieving the optimal solution and decreasing the side lobe level. To obtain the optimal solution, thinning is performed by removing some elements in an array through stimulating the zero state or setting off those elements. In this paper, a 100-elements linear array and a 100-elements planar array with isotropic elements are investigated. Thinning is performed using Genetic, Particle Swarm, Imperialist Competitive and Grey Wolf algorithms. The Imperialist Competitive and Grey Wolf algorithms have been suggested in this paper for thinning a full array in order to compare their performance with the performance of other evolutionary algorithms suggested in previous studies. The results show that the Grey Wolf algorithm has a better performance in terms of reaching the lowest side lobe level. It is also found that by using Grey Wolf algorithm, it would be possible to reach a level of -19.31 dB side lobe for a linear array and a level of -48.96 dB side lobe for a planar array.